Análisis de los métodos mecánicos, químicos, y físicos del cuidado de las prótesis dentales para la prevención de patologías orales. revisión sistemática - Toapanta Cali, Anabel Vanessa (2025)
Introduction: Partial or total edentulism is considered permanent tooth loss, which generates changes in the masticatory function of the mouth, the general state of health and the quality of life of the patient, so dental prostheses are used to help these patients. However, poor care will lead to the formation of biofilms that generate a considerable loss in the concentration of mechanical properties of the prosthetic material, in addition to the appearance of inflammatory processes in underlying tissues which could jeopardize the remaining dental pieces. Objective: To analyze the mechanical, chemical and physical methods of dental prosthesis care for the prevention of oral pathologies by means of a literature review and thereby provide information to improve the health of prosthesis users. Method: Systematic review with a qualitative and descriptive approach, using the documentary review method to compile scientific articles from the Pubmed, Wiley and LILACS databases, where advanced search strings were used. Results: 162 articles were found, of which only 12 were selected as valid for the research. Moreover, the use of a toothbrush was identified as the most common. Conclusions: By analyzing the mechanical, chemical and physical methods of denture care for the prevention of oral pathologies, it could be determined that all three methods are effective for the reduction of microorganisms present in dentures, which favors the oral health care of patients wearing dentures.